Survival Following Traumatic Ventricular Rupture and Prolonged Ambulance Transport in a Patient With Previous Coronary Artery Bypass Surgery. Issue 6 (15th August 2013) - Juvet, Tristan; Al‐Khalifa, Abdulwahab; Singh, Steve K.
Abstract Patients presenting with traumatic cardiac rupture are unlikely to survive lengthy transfers from the trauma scene to a hospital. However, in patients with a previous sternotomy, adhesions may divert cardiac hemorrhage, allowing hemodynamic management to be successful. We present an 83‐year‐old male with a history of coronary artery bypass grafting (CABG) who sustained a right ventricular rupture. He underwent an immediate redo sternotomy and was discharged 10 days postoperatively with no complications. doi: 10.1111/jocs.12183 (J Card Surg 2013;28:684–686)